The development of small and medium business: of Kazakhstan and foreign experience - Ozpence, O.; Madiyarova, E.S.; Konurbayeva, Zh.T.; Eckert, A. (BUKETOV BUSINESS REVIEW, 2017)
The article presents the results of research of tendencies of development of domestic small and medium-sized businesses, assessed in comparison with other countries. Comparative analysis of the development of the SME sector of Kazakhstan and other countries shows noticeable gap in our country on such indicators as the contribution of SMEs to GDP and employment. World experience shows that if the state wants to develop dynamically and steadily, its socio-economic programs should always include measures to stimulate small and medium business. The experience of foreign countries shows that the main financial instrument of the innovation policy in SMEs is the use of state budget funds, although the indirect tool of state support for research and development through tax incentives is also important. Thus, the leading role of the state in the development of the innovation process should manifest itself not only in direct funding, but tax incentives and high-tech business, and in encouragement of investment in high-tech industry. The role of small business innovation is determined by such important aspects as a contribution to the production of GDP, the impact on the structure of the economy, creating a competitive environment, the growth of effective demand, the development of scientific and technological progress, as well as in solving social and political problems. In the current difficult situation it SMEs can act as a stabilizer, and therefore entitled to the appropriate attention of society and state.